In vitro evaluation of Ficoll‐enriched and genipin‐stabilised collagen scaffolds. (2nd May 2012) - Satyam, A.; Subramanian, G. S.; Raghunath, M.; Pandit, A.; Zeugolis, D. I.
Abstract Polysaccharides are frequently incorporated into scaffolds for tissue engineering applications to improve mechanical and biological properties. We evaluated the influence of a Ficoll® scaffold on collagen films, a scaffold that is extensively used for soft and hard tissue repair. To avoid cytotoxicity issues associated with chemical reagents, the influence of genipin, a naturally occurring crosslinking agent, was assessed. Ultra‐structural level collagen films formed with and without Ficoll showed a fine fibrillar structure whereas genipin crosslinked films showed a coarse fibrillar and partially nodular structure. In contrast, glutaraldehyde crosslinked films lost their fibrillar pattern. Crosslinking significantly increased denaturation temperature (p < 0.001), stress (p < 0.0001) and force (p < 0.0001) at break. Collagen/Ficoll and collagen/Ficoll/genipin films showed the highest WI38 fibroblast attachment than any other scaffold (p < 0.003) and significantly greater WI38 fibroblast metabolic activity than other scaffolds (p < 0.001). By day 6. collagen/Ficoll/genipin films also induced higher and more aligned fibronectin matrix deposition than other scaffolds. Overall, this study indicates the suitability of collagen/Ficoll/genipin for tissue engineering applications. Copyright © 2012 John Wiley & Sons, Ltd.